Juridical Approach to Legal Protection For The Public Of Illegal Peer To Peer Lending Users - Lyanthi, Merline Eva (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2024)
Technology that is developing quickly is utilized in all fields to provide convenience including financial transactions. But, there are also illegal financial transactions called peer – to peer (P2P) lending that do not have a license. The illegal loan operators have access to personal data owned by victims as application users. It is not uncommon to find some illegal loan operators who create conflicts against application users. This research aims to review the legal protection forpeople who use illegal peer to peer lending in Indonesia. This research uses normative law research method, while the research approach uses normative juridical approach. This data of research is secondary data analyzed with aqualitative approach. This research resulted in the existence of criminal law policiesthat used to punish illegal peer – to peer lending for their actions are using Law Number 8 of 1999 because of the position of the public as users of online loans as consumers and Law Number 19 of 2016 concerning Amendments to Law Number11 of 2008 concerning ITE because transactions are carried out using electronic media.